Envenoming caused by a Portuguese man-o'-war (Physalia physalis) manifesting as purpuric papules Envenenamento por caravela (Physalia physalis) manifestando-se com erupção papulopurpurica - Yamin José Risk; João Luiz Costa Cardoso; Vidal Haddad Junior (Sociedade Brasileira de Dermatologia, 2012)
We report the case of a 42-year old woman who was envenomed by a Portuguese man-o'-war (Physalia physalis). She presented an anomalous reaction manifested by purpuric papules that appeared after the initial phase of envenoming (around 24 hours later), when linear erythematous and edematous papules were observed. Late-onset reactions in accidents involving cnidarians commonly include chronic eruptions and local pigmentation. Os autores relatam um envenenamento causado por um cnidário, a caravela (Physalia physalis), em uma mulher de 42 anos. A paciente apresentou uma reação incomum manifestada por pápulas purpúricas surgidas após a fase inicial de envenenamento (cerca de 24 horas depois) quando foram observadas pápulas lineares edematosas e eritematosas. As reações tardias nos acidentes por cnidários comumente apresentam erupções recorrentes e pigmentações locais.